Lead levels in primary teeth of children living in Mexico City - J. C. HERNÃƒÆ’Ã‚ÂNDEZ-GUERRERO, M. D. JIMÃƒÆ’Ã¢â‚¬Â°NEZ-FARFÃƒÆ’Ã‚ÂN, R. BELMONT, C. LEDESMA-MONTE (Paediatric Dentistry, 2004)
Lead toxicity to humans has been a field of debate among researchers.